Management Accounting Strategies in Supporting Business Sustainability and Green Accounting - Dina Amalya Putri (CV Edujavare Publishing, 2026)
The increasing global emphasis on sustainable development has encouraged organizations to integrate environmental and social considerations into their business strategies and accounting practices. This study aims to examine the role of management accounting strategies in supporting business sustainability and green accounting. Using a literature review approach, this research analyzes and synthesizes findings from scholarly articles, books, and relevant reports related to management accounting, sustainability accounting, and environmental management practices. The findings indicate that management accounting has evolved beyond its traditional focus on financial performance to become a strategic tool that supports sustainable decision-making through planning, performance measurement, cost management, and resource optimization. In addition, green accounting contributes to environmental responsibility by identifying, measuring, and reporting environmental costs and impacts associated with organizational activities. The integration of management accounting strategies and green accounting enables organizations to improve decision-making quality, enhance resource efficiency, strengthen sustainability reporting, and increase stakeholder accountability. Furthermore, this integration supports the achievement of long-term business sustainability by balancing economic objectives with environmental stewardship and social responsibility. The study concludes that the synergy between management accounting and green accounting provides a comprehensive framework for sustainable business performance and serves as a critical factor in achieving competitive advantage and sustainable development in the modern business environment.